GAUSSIAN DISTRIBUTION OF BREAKDOWN SHOTS IN NON-UNIFORM FIELDS - John Tarilanyo Afa (European Scientific Journal, ESJ, 2014)
The work is aimed at investigating the pattern of breakdown in an airgap for nonuniform field. In most technical literature it has been stated in gas breakdown that in the surrounding gas, photoelectrons are produced which initiates auxiliary avalanches directed towards the stem of the main avalanche, and that the greatest multiplication in these avalanches occur along the axis of the main where the space charge field supplements the external field. Before the complete streamer formation (plasma) several breakdowns could occur before the breakdown of the main avalanche. This breakdown occurs in a definite manner due to presence of the applied field. In order to investigate the pattern of breakdown four point-plane electrodes were used. For every test a kraft paper was placed on the plate electrode and each breakdown shot from the test punches a hole on the paper. After each complete experiment with punches on the paper, circles with intervals of 5mm where drawn until all the punches have been enclosed. From the analyses it was seen that for all point-plane electrodes the shot takes the Gaussian form of distribution within the ionization zone of electrode gap. This form of breakdown is mostly influenced by the resultant field between the external field and the space charge field at the head of the avalanche.